Coordination Degree between International Business and Ecosystem under the Background of Global Supply Chain Reconstruction - Lixi Yin (Tehnički Vjesnik)
China occupies a key part of the global supply chain for the assembly of raw materials, intermediate goods and finished products. As a major global consumer market, China has become the end of major supply chains. China's traditional commodity production mode, large-scale production and processing of cheap export commodities at the cost of the ecosystem, are resulting in the development of international commerce and ecosystem imbalance. Aiming at the CD of international commerce and ecosystem, this paper calculates the coordination degree (CD) of different areas in China, which conducts a spatial autocorrelation test. The results show that the data of international commerce from 2012 to 2021 are obtained, the index value of international commerce CD under the background of global supply chain is comprehensively calculated, and the coordination between international commerce and ecosystem in China is analyzed from the perspective of global supply chain reconstruction. The results show that there is a large gap in the CD of international commerce and the trade structure is unstable in the global supply chain reconstruction. Finally, China's international business CD is at the primary and intermediate coordination stage, with stable development over the years, and the development level of ecosystem is higher than that of international business.